Exergy assessment of a multistage multi-evaporator vapor compression refrigeration system using eighteen refrigerants - Prateek D. Malwe (Energy Reports, 2022)
The use of lower global warming potential refrigerants as an alternative to hydrochlorofluorocarbons and hydrofluorocarbons from an environmental perspective is the need of an hour. The feasibility and possibility of alternative refrigerants in the existing refrigeration system can be recognized using exergy assessment. This will lead to improving the thermal performance of the refrigeration systems. In this paper, exergy assessment of a multistage multi-evaporator vapor compression refrigeration system is performed using the Simulink model. A total of eighteen refrigerants are considered for the analysis from the environmental perspective, safety considerations, etc. The evaporator-1, evaporator-2, and condenser temperatures are varied from 0 °C to 15 °C, −15 °C to −5 °C, and 25 °C to 33 °C respectively. The highest exergy destruction among all the components is found for both the compressors, followed by the condenser, evaporators, expansion devices, and internal heat exchanger. Refrigerants R141b, R123, R245ca, R245fa, and R152a showed better thermal performance than hydrofluoroolefins refrigerants, but have high GWP values. R1234ze(E), and R1234yf are environmentally friendly and achieved similar performance to conventional refrigerants.